Low Molecular Weight Mannogalactofucans Derived from Undaria pinnatifida Induce Apoptotic Death of Human Prostate Cancer Cells In Vitro and In Vivo - Lee, Jisun; Lee, Seul; Synytsya, Andriy; Capek, Peter; Lee, Chang Won; Choi, Ji Won; Cho, Sarang; Kim, Woo Jung; Park, Yong Il (Marine biotechnology, 2018)
Low molecular weight mannogalactofucans (LMMGFs) prepared by enzymatic degradation of high molecular weight Undaria galactofucan (MF) were evaluated for their anti-cancer effects against human prostate cancer. Correlation NMR and linkage analyses confirmed that LMMGFs consist mainly of α-fucose and β-galactose units: α-fucose units are 1,3-linked; β-galactose units are terminal, 1,3- and/or 1,6-linked; both sugars are partially sulphated, fucose at positions O-2 and/or O-4 and galactose at O-3. Mannose residue, as a minor sugar, presents as the 1,4-linked terminal units. LMMGFs more significantly induced cell cycle arrest at the G0/G1 phase and cell death via suppression of the Akt/GSK-3β/β-catenin pathway than MF in human PC-3 prostate cancer cells. LMMGFs upregulated mRNA expression of death receptor-5 (DR-5), the ratio of Bax to Bcl-2, the cleavage of caspases and PARP, the depolarisation of mitochondrial membrane potential, and ROS generation. LMMGFs (200-400 mg/kg) effectively reduced both tumour volume and size in a xenografted mouse model. These results demonstrated that LMMGFs attenuate the growth of human prostate cancer cells both in vitro and in vivo, suggesting that LMMGFs can be used as a potent functional ingredient in health-beneficial foods or as a therapeutic agent to prevent or treat androgen-independent human prostate cancer. Graphical Abstract.
Keywords: Animals; beta-katenin; apoptóza; Membrane Potential, Mitochondrial; Apoptosis; polysacharidy; lidé; Cell Cycle Checkpoints; kontrolní body buněčného cyklu; Mice; Glycogen Synthase Kinase 3 beta; messenger RNA; nádory prostaty; myši; Prostatic Neoplasms; RNA, Messenger; molekulová hmotnost; Male; membránový potenciál mitochondrií; Undaria; kinasa glykogensynthasy 3beta; zvířata; mužské pohlaví; Molecular Weight; beta Catenin; Polysaccharides; Humans